The subclinical effect of celiac disease on the heart and the effect of gluten-free diet on cardiac functions - Karadaş, Ulaş; Eliaçık, Kayı; Baran, Maşallah; Kanık, Ali; Özdemir, Nihal; İnce, Osman Tolga and Bakiler, Ali Rahmi (The Turkish Journal of Pediatrics, 2016)
This study aimed to investigate the effects of celiac disease (CD) on cardiac function in children by using conventional transthoracic echocardiography (TTE) and tissue Doppler echocardiography (TDE). Forty-nine patients diagnosed with CD were enrolled into the study. Group 1 consisted of 26 (53%) patients who had recently been diagnosed and had not been on gluten-free diet whereas Group 2 consisted of 23 (47%) patients who had been on regular gluten-free diet for at least 10 months. 20 healthy children were enrolled into the study as the control group. The deceleration time (DT) and the left ventricle (LV) isovolumetric relaxation time (IVRT) were significantly shorter in Group 1 compared to Group 2 and the control group (p=0.002, p=0.015). Mitral valve E/E’ ratio was significantly lower in Group 1 and 2 when compared to the control group (p < 0.001). The study demonstrated that evaluation of these parameters by using TDE could be beneficial in the early diagnosis of cardiac involvement in children with CD.